2015
DOI: 10.1099/jmm.0.000014
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for assessing the cross-protective efficacy of oral non-typhoidal Salmonella vaccine candidates harbouring in-frame deletions of the ATP-dependent protease lon and other genes

Abstract: In BALB/c mouse models of Salmonella enterica serovar Typhimurium infection, a single oral immunization with a mutant strain with an insertion of the chloramphenicol resistance gene into the ATP-dependent protease clpP or lon gene decreased the number of salmonellae in each tissue sample 5 days after oral challenge with virulent S. Typhimurium at weeks 26 and 54 postimmunization. These data suggested that an oral immunization with the ClpP-or Lon-disrupted S. Typhimurium strain could provide long-term protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…SPI-1 knock-down bacteria were constructed with an in-frame deletion of sipB , a transcriptional activator of SPI-1. An Flp recombination target (FRT)-flanked chloramphenicol-resistant marker cassette (KD3) fragment was amplified using the primers 5′-GTGTAGGCTGGAGCTGCTTC-3′ (forward) and 5′-ATGGGAATTAGCCATGGTCC-3′ (reverse) [ 56 ], and the PCR products were inserted into pGFPmut 3.1 (Clonetech, cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…SPI-1 knock-down bacteria were constructed with an in-frame deletion of sipB , a transcriptional activator of SPI-1. An Flp recombination target (FRT)-flanked chloramphenicol-resistant marker cassette (KD3) fragment was amplified using the primers 5′-GTGTAGGCTGGAGCTGCTTC-3′ (forward) and 5′-ATGGGAATTAGCCATGGTCC-3′ (reverse) [ 56 ], and the PCR products were inserted into pGFPmut 3.1 (Clonetech, cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…Although we do not have a WHO recommended vaccine for prevention of iNTS disease there have been a number of initiatives that have led to the development of promising vaccine candidates that may play a major role in management and control of iNTS disease in endemic areas [65,66]. …”
Section: Invasive Non-typhoidal Salmonella (Ints) Diseasementioning
confidence: 99%
“…Studies that have examined cross-protection elicited by Salmonella vaccines have shown mixed results with some reports describing cross-protection against heterologous challenge organisms and others reporting no protection. [24, 99103] Similarly, volunteer studies have shown that immune responses generated by live S . Typhi vaccines are cross-reactive with other Salmonella serovars but it is not yet known whether these responses would be protective.…”
Section: Live Attenuated Vaccines Against Invasive Salmonella Seromentioning
confidence: 99%